Simplifications of the Rule base for the stabilization of Inverted Pendulum System - Tharwat O. S. Hanafy; Mohamed K Metwally (Institute of Advanced Engineering and Science, 2014)
Control of an inverted pendulum on a carriage which moves in a horizontal path, is one of the classic problems in the area of control. The basic aim of our work was to design appropriate controller to control the angle of the pendulum and the position of the cart in order to stabilize the inverted pendulum system. The main objective of this paper to keep the stabilization of the inverted pendulum based on the simplification of rule base. The proposed fuzzy control scheme successfully fulfills the control objectives and also has an excellent stabilizing ability to overcome the external impact acting on the pendulum system. The effectiveness of this controller is verified by experiments on a simple inverted pendulum with fixed cart length.